African yam bean: a food security crop? - Adewale, B.D. (2010)
This paper fouses on the conservation and maintenance of agrobiodiversity of neglected and underutilized plant species, such as the African yam bean (Sphenostylis stenocarpa) in seed banks to contribute to food security and prevent a potential food crisis. The potentials and biodiversity of various African yam bean accessions are also highlighted. Results of diversity, productivity, stability and breeding studies of African yam bean accessions in Nigeria using morphological and molecular methods are also presented.